A Comparative Study of Enantioseparations of Nα-Fmoc Proteinogenic Amino Acids on Quinine-Based Zwitterionic and Anion Exchanger-Type Chiral Stationary Phases under Hydro-Organic Liquid and Subcritical Fluid Chromatographic Conditions - Gyula Lajkó; Nóra Grecsó; Gábor Tóth; Ferenc Fülöp; Wolfgang Lindner; Antal Péter; István Ilisz (Molecules, 2016)
The focus of this contribution is a comparative investigation of enantioseparations of 19 Nα-Fmoc proteinogenic amino acids on Quinine-based zwitterionic and anion-exchanger type chiral stationary phases employing hydro-organic and polar-ionic liquid and subcritical fluid chromatographic conditions. Effects of mobile phase composition (including additives, e.g., water, basis and acids) and nature of chiral selectors on the chromatographic performances were studied at different chromatographic modes. Thermodynamic parameters of the temperature dependent enantioseparation results were calculated in the temperature range 5–50 °C applying plots of lnα versus 1/T. The differences in standard enthalpy and standard entropy for a given pair of enantiomers were calculated and served as a basis for comparisons. Elution sequence in all cases was determined, where a general rule could be observed, both in liquid and subcritical fluid chromatographic mode the d-enantiomers eluted before the L ones. In both modes, the principles of ion exchange chromatography apply.